Evaluation of in-person and on-line food safety education programs for community volunteers. (May 2019) - Yeung, Henry Fan; Bruhn, Christine; Blackburn, Mary; Ganthavorn, Chutima; Martin, Anna; Mendoza, Concepcion; Neelon, Marisa; Smith, Dorothy; Soule, Katherine; Spezzano, Theresa Marie; Barrett, Tressie; Feng, Yaohua
Abstract: The goal of "Make it Safe, Keep it Safe" is to educate volunteers who prepare food for community events about proper handling of food to prevent foodborne illness. A food safety curriculum was delivered either via an in-person workshop or by accessing the material on line from a personal computer. Food safety materials were based upon existing Food and Drug Administration food safety guidelines. University of California Extension Advisors taught the in-person food safety education and recruited participants for the on-line training. Volunteers (n = 242) who prepared food for 4-H programs, churches, service clubs, senior centers or other community activities completed either the on-line or in person workshop. Food safety knowledge was assessed via a pre- and post-survey. Both online and workshop education improved the food safety knowledge of participants and overall there was no significant difference found in the level of knowledge gained from the two formats. The findings have implications for when and how food safety can be taught. The future goal for this project is to promote "Make it Safe, Keep it Safe" as an online food safety education tool for use by Cooperative Extension and other educators. Highlights: Community food volunteers need more food safety education. The food safety education program improved participants' food safety knowledge. Online module was as effective as in-person workshop.